The Dynamic Characteristics of Soil Macrofauna in Chloris Virgata Habitat in Songnen Grassland - 孙立娜; 殷秀琴; 王振海; 单昱 (Hans Journal of Agricultural Sciences, 2012)
大型土壤动物是陆地生态系统中的重要组成部分，为探讨松嫩草原虎尾草生境大型土壤动物组成及多样性动态特征，于 2006 年 5 月、 7 月和 9 月进行了调查研究，共获得大型土壤动物 427 只，隶属 2 门 4 纲 9 目 22 科，优势类群共 3 类，为象甲科幼虫、步甲科和蜘蛛目，类群数与个体数在各月份间无显著差异。大型土壤动物在垂直分布上具有明显的表聚性，各层与各月间均存在显著差异。大型土壤动物的多样性指数随季节变化不大，其中 9 月份多样性指数、丰富度指数、优势度指数最大， 7 月份均匀性指数达到最大值。 Soil fauna play an important role in terrestrial ecosystems ， in order to investigate the diversity of soil macrofauna in Chloris virgata habitat in Songnen grassland, investigations were conducted in the western of Jilin Province in May, July and September 2006. A total of 427 individuals, belonging to 2 phylas, 4 classes, 9 orders and 22 families, were obtained. There were no significant differences both in groups and individuals among 3 dominant groups, which were Curculionidae larvae, Carabidae and Araneida. Soil macrofauna was decreasing obviously with the depth of soil layers, and that there were significant differences among layers and months. The seasonal variations of the diversity indices of soil macrofauna were not significant. In these diversity indices, Shannon-Wiener diversity index, Margalef richness index, Simpson dominance index were highest in September, however Pielou evenness index was higher in July.